2016
DOI: 10.1016/j.polymer.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

A facile chemoenzymatic synthesis of amphiphilic miktoarm star copolymers from a sugar core and their potential for anticancer drug delivery

Abstract: Miktoarm star copolymers, which are in the simplest form of branching, are particularly of interest to biomedical applications. Nevertheless, their synthesis is facing troubles of seeking inner cores with heterogeneous functional groups as well as tedious protection and deprotection. Herein, ethyl-β-D-glucopyranoside, a sugar molecule containing homogeneous groups, was directly employed as a core to synthesize an amphiphilic miktoarm star copolymer via a chemoenzymatic approach without complicated decoration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The self‐assembly of block copolymers is a promising area of polymer chemistry and engineering with technological applications in drug and vaccine delivery, sensing, catalysis, and more. The self‐assembly of block copolymers depends on many factors, including polymer architecture, amphiphilicity, polymer molecular weights, and polymer functionality .…”
Section: Introductionmentioning
confidence: 99%
“…The self‐assembly of block copolymers is a promising area of polymer chemistry and engineering with technological applications in drug and vaccine delivery, sensing, catalysis, and more. The self‐assembly of block copolymers depends on many factors, including polymer architecture, amphiphilicity, polymer molecular weights, and polymer functionality .…”
Section: Introductionmentioning
confidence: 99%
“…reported on a study using A(AB) 3 star polymers synthesized from an oligosaccharide core, ethyl‐ β ‐ d ‐glucopyranoside, where A = PCL 2800 , A′ = PCL 3100 , and B = PEG 2000 or PEG 5000 (numbers denote the molecular weight of the polymer). [ 68 ] Using Novozyme 435 as the catalyst, they managed to carry out selective ring‐opening of ε ‐caprolactone (CL) to obtain the asymmetric star copolymers. It was observed that with the increase in hydrophilic fraction from PEG 2000 to PEG 5000 , the hydrodynamic diameter decreased from 107 to 72 nm ( Figure 4 ), while the CMC increased from 0.90 to 3.45 µg mL −1 (Table 2).…”
Section: Strategies To Design Branched Star Copolymers For Drug Deliverymentioning
confidence: 99%
“…Depending on the core structure, 1 H NMR spectra can also provide more accurate confirmation of initiator usage, as with the disappearance of the corresponding protons [ 59 , 63 ]. For example, ethyl-β-d-glucopyranoside, a sugar (containing one secondary and three primary hydroxyls) was used to initiate the ROP of caprolactone, specifically at its secondary hydroxyl group, with the aid of the catalyst Novozyme 435.…”
Section: Synthetic Approaches To Miktoarm Star Polymersmentioning
confidence: 99%